Pembuatan WebGIS Sebagai Visualisasi Informasi Potensi Desa - Adkha Yulianandha Mabrur; Alifah Noraini; Irvania Sukma Kumala (Universitas Pendidikan Ganesha, 2023)
Geographic Information System (GIS) is a computer system designed to perform a job related to various kinds of spatial information data. The system runs with various capabilities, such as stamping, checking, integrating data, manipulating, analyzing and presenting data from various spatial data information as a reference for the condition of the earth. Information related to these spatial conditions needs to be shared through an effective system called Web Technology. WebGIS technology has the purpose of sharing information based on GIS using internet services, namely the web. WebGIS answers various kinds of complex mapping presentation problems, simplifying it so that it makes it easier for users to get information. This is what underlies the creation of WebGIS in Sumberejo Village, the need to share information related to objects in the village easily. The survey data is then carried out data processing, editing spatial and attribute data, as well as adding supporting data related to information to be visualized in web form. The results of the information presented in WebGIS are that there are five categories ranging from tourist attractions with a total of 10 points, places of worship 9 points, health 9 points, education 9 points and places to eat 18 points. The WebGIS can be accessed via https://sumberejo.gis.co.id with a simple appearance and easy to operate so that it is expected to make it easier for local users. So that later it can be developed in terms of updating data to make it more informative